Saint James' Palace
At the center of many Tudor palaces-Greenwich, Hampton Court, Hatfield, and Nonesuch-lies St. James' Palace, which, for 140 years, was the royal residence. Most of the original buildings have been replaced over the centuries, but the gatehouse still stands with its four octagonal towers. Henry VIII took an interest in building, particularly for domestic use, and introduced foreign designers: Da Trivigi was appointed Court Architect; Torrigiani, the sculptor, was commissioned to design Henry's father's tomb; Holbein, the painter was also in Henry's employ although, oddly, he did not establish a following. Altogether, their influence enriched, rather than changed, the course of English architecture at this time.